Benefits of remote real-time side-effect monitoring systems for patients receiving cancer treatment - Sarah Kofoed; Sibilah Breen; Karla Gough; Sanchia Aranda (Frontiers Media S.A., 2012)
In Australia, the incidence of cancer diagnoses is rising along with an aging population. Cancer treatments, such as chemotherapy, are increasingly being provided in the ambulatory care setting. Cancer treatments are commonly associated with distressing and serious sideeffects and patients often struggle to manage these themselves without specialized real-time support. Unlike chronic disease populations, few systems for the remote real-time monitoring of cancer patients have been reported. However, several prototype systems have been developed and have received favorable reports. This review aimed to identify and detail systems that reported statistical analyses of changes in patient clinical outcomes, health care system usage or health economic analyses. Five papers were identified that met these criteria. There was wide variation in the design of the monitoring systems in terms of data input method, clinician alerting and response, groups of patients targeted and clinical outcomes measured. The majority of studies had significant methodological weaknesses. These included no control group comparisons, small sample sizes, poor documentation of clinical interventions or measures of adherence to the monitoring systems. In spite of the limitations, promising results emerged in terms of improved clinical outcomes (e.g. pain, depression, fatigue). Health care system usage was assessed in two papers with inconsistent results. No studies included health economic analyses. The diversity in systems described, outcomes measured and methodological issues all limited between-study comparisons. Given the acceptability of remote monitoring and the promising outcomes from the few studies analyzing patient or health care system outcomes, future research is needed to rigorously trial these systems to enable greater patient support and safety in the ambulatory setting.